Making a business plan for starting a transitional pain service within the US healthcare system. Issue 8 (20th April 2021) - Sun, Eric C; Mariano, Edward R; Narouze, Samer; Gabriel, Rodney A; Elsharkawy, Hesham; Gulur, Padma; Merrick, Sharon K; Harrison, T Kyle; Clark, J David
Abstract : Chronic pain imposes a tremendous economic burden of up to US635 billion per year in terms of direct costs (such as the costs of treatment) and indirect costs (such as lost productivity and time away from work). In addition, the initiation of opioids for pain is associated with a more than doubling of pharmacy and all-cause medical costs. The high costs of chronic pain are particularly relevant for anesthesiologists because surgery represents an inciting event that can lead to chronic pain and long-term opioid use. While the presence of risk factors and an individual patient's postoperative pain trajectory may predict who is at high risk for chronic pain and opioid use after surgery, to date, there are few interventions proven to reduce these risks. One promising approach is the transitional pain service. Programs like this attempt to bridge the gap between acute and chronic pain management, provide continuity of care for complicated acute pain patients after discharge from the hospital, and offer interventions for patients who are on abnormal trajectories of pain resolution and/or opioid use. Despite awareness of chronic pain after surgery and the ongoing opioid epidemic, there are few examples of successful transitional pain service implementation in the USA. Key issues and concerns include financial incentives and the required investment from the hospital or healthcare system. We present an economic analysis and discussion of important considerations when developing a business plan for a transitional pain service.